Использование формально-логических методов для описания признаков излучающих объектов и их состояний в экспертных системах оценки радиоэлектронно-объектовой обстановки - Рось, А. А.; Калюжный, Н. М.; Смилык, В. И.; Су Джихуй (ХНУРЭ, 2008)
Possibility is considered of the use of formal-logical methods for cecognition of objects in the consulting models of estimation of radio electronic situation. It is shown, that on comparison with by the traditional methods of recognition on the basis of neural networks formal- logical methods allow to work with the sign spaces of large dimensions and by the presence of methods of treatment of a priori and a posteriori vagueness in the process of functioning of the system of recognition.